1998
DOI: 10.1097/00002030-199807000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant responses to triple combination antiretroviral therapy in advanced HIV disease

Abstract: Our observations of discrepant immunological and virological responses to treatment raise the issue of the significance of persistent elevated levels of plasma HIV RNA and of the relevance of measurements of plasma viral load for assessing the efficacy of antiretroviral therapy in patients whose CD4 cell counts increase despite the absence of significant decrease in plasma HIV viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(108 citation statements)
references
References 12 publications
4
100
1
3
Order By: Relevance
“…Recently, it has been recognized that a significant proportion of treated patients exhibit no clinical evidence of disease progression, with stable or increasing T cell counts in spite of the presence of viral load rebound [38]. Interestingly, the five patients in our study presenting such features were shown to correct the increased levels of CD40L and OX40 under HAART.…”
Section: Discussionmentioning
confidence: 49%
“…Recently, it has been recognized that a significant proportion of treated patients exhibit no clinical evidence of disease progression, with stable or increasing T cell counts in spite of the presence of viral load rebound [38]. Interestingly, the five patients in our study presenting such features were shown to correct the increased levels of CD40L and OX40 under HAART.…”
Section: Discussionmentioning
confidence: 49%
“…Whether this effect is significant in vivo has been disputed, 66 yet it is supported by several distinct lines of evidence: (1) enhanced CD4 ϩ T-cell levels with PI-containing versus -sparing regimens that achieve equivalent suppression of viral replication, 10,67 (2) increases in CD4 ϩ T-cell number despite no observable antiviral effect, [11][12][13] (3) greater increases in CD8 ϩ T-cell number after initiation of PI therapy than non-PI therapy, 68 and (4) dramatic decreases in CD4 ϩ T-cell number after discontinuation of PIcontaining therapy, even when PI therapies were unsuccessful in achieving viral suppression. 11,69 Together with in vitro observations of antiapoptotic effects, these observations argue in favor of a clinically significant effect of PI-containing therapy on CD4 ϩ T-cell number as compared with PI-sparing therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Although increases in CD4 T-cell counts typically occur in parallel with a reduction in viral replication, these effects may be seen before significant changes in plasma RNA levels 9 or in the absence of antiviral effect. [10][11][12][13] These and other findings suggest that the protease inhibitor (PI) class of drugs may influence T-cell turnover in a manner that is independent of their role in viral suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5]12,14,[19][20][21][22][23] Of note, not only CD4 ϩ T-cell number and quality are impaired in HIV infection, but many functions of many immune cells may be impaired, and not fully recovered under HAART. For instance, plasmacytoid dendritic cell and natural killer cell activities have been reported to remain incompletely reconstituted after 1 year of effective antiretroviral therapy.…”
Section: Immunologic Responses To Haart: Both Quality and Quantity Mamentioning
confidence: 99%